1997
DOI: 10.1046/j.1365-3040.1997.d01-142.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gas transport through rice cultivars on methane emission from rice paddy fields

Abstract: Two Italian rice {Oryza sativa var. japonica) cultivars, Lido and Roma, were tested in the field tor methane production, oxidation and emission. In two consecutive years, fields planted with the rice eultivar Lido showed methane emissions l'\-'i\% lower than fields planted with the eultivar Roma. This differenee was observed irrespective of fertilizer treatment. In eontrast to methane emissions, differenees in methane production or oxidation 'were not observed between fields planted with the two eultivars. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(112 citation statements)
references
References 28 publications
3
109
0
Order By: Relevance
“…Indeed, the decline in CH 4 emissions at the later stages of rice growth (Fig. 3e) might be attributed to the gradual increase of CH 4 oxidation and inhibition of methanogenesis due to radial oxygen loss by rice root system (De Bont et al 1978;Gerard and Chanton 1993;King 1996); or by the increasing contribution of plant mediated CH 4 emissions through rice aerenchyma, which we could not account for with our methodological approach (Butterbach-Bahl et al 1997). Overall, the dissolved O 2 concentration in the pore-water of the surface peat was a strong driver of both CH 4 and N 2 O emissions in situ, accounting for 40 and 20 % of the variance in fluxes for the two gases, respectively (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the decline in CH 4 emissions at the later stages of rice growth (Fig. 3e) might be attributed to the gradual increase of CH 4 oxidation and inhibition of methanogenesis due to radial oxygen loss by rice root system (De Bont et al 1978;Gerard and Chanton 1993;King 1996); or by the increasing contribution of plant mediated CH 4 emissions through rice aerenchyma, which we could not account for with our methodological approach (Butterbach-Bahl et al 1997). Overall, the dissolved O 2 concentration in the pore-water of the surface peat was a strong driver of both CH 4 and N 2 O emissions in situ, accounting for 40 and 20 % of the variance in fluxes for the two gases, respectively (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Emissions are also determined by the number of crops per year and the total area under cultivation, which is a function of the demand for rice, and the amount of rice produced per hectare, known as the 'yield'. Practices such as occasional draining of the fields, the addition of oxidents or other mineral fertilizers, and selection of low-CH 4 cultivars have been found to reduce emissions by approximately 40-55%, 20-70% and up to 60%, respectively (EPA, 1994;Neue et al, 1997;Sigren et al, 1997;Yagi et al, 1997;Butterbachbahl et al, 1997;Cole et al, 1997;Mitra et al, 1999). Alternatively, the addition of organic fertilizers has the potential to increase emissions by over 50% relative to non-organic fertilizers (e.g., Buendia et al, 1997;Denier van der Gon & Neue, 1995;Yagi et al, 1997).…”
Section: Termites 13%mentioning
confidence: 99%
“…While the implementation of certain mitigation options by producers may be restricted due to required changes in management practices and equipment or the possibility of yield reductions, the selection of low-emitting cultivars can be implemented without major changes in crop management while maintaining grain yields. Studies have indicated that about 90% of CH 4 emissions from rice fields occur by plant-mediated transport through the aerenchyma tissues of rice plants [16,19,23,24]. Due to the strong influence of rice plants themselves on CH 4 emissions from the system, innate physiological differences between cultivars may lead to differences in CH 4 transport capacities [23], differences in biomass accumulation [25] and root exudation [26,27,28], or differences in microbial populations in the rhizpsphere [29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that about 90% of CH 4 emissions from rice fields occur by plant-mediated transport through the aerenchyma tissues of rice plants [16,19,23,24]. Due to the strong influence of rice plants themselves on CH 4 emissions from the system, innate physiological differences between cultivars may lead to differences in CH 4 transport capacities [23], differences in biomass accumulation [25] and root exudation [26,27,28], or differences in microbial populations in the rhizpsphere [29]. Many studies throughout rice-growing countries have reported differences in CH 4 emissions among rice cultivars; however, the complexity of the system and processes involved have led to differing results and, at this point, no single parameter has been identified to consistently explain differences in CH 4 emissions among cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation